2014
DOI: 10.1128/aem.02284-14
|View full text |Cite
|
Sign up to set email alerts
|

Circular Bacteriocins: Biosynthesis and Mode of Action

Abstract: b Circular bacteriocins are a group of N-to-C-terminally linked antimicrobial peptides, produced by Gram-positive bacteria of the phylum Firmicutes. Circular bacteriocins generally exhibit broad-spectrum antimicrobial activity, including against common food-borne pathogens, such as Clostridium and Listeria spp. These peptides are further known for their high pH and thermal stability, as well as for resistance to many proteolytic enzymes, properties which make this group of bacteriocins highly promising for pot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
147
0
12

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 131 publications
(160 citation statements)
references
References 60 publications
1
147
0
12
Order By: Relevance
“…Between 5 and 7 genes appear to be needed, although some others, clustered with them, might play a role as well (Maqueda et al 2008;Gabrielsen et al 2014). Most proteins are hydrophobic, thus suggesting that bacteriocin synthesis is membrane associated.…”
Section: Genetics and Regulation Of Bacteriocin Synthesismentioning
confidence: 95%
See 1 more Smart Citation
“…Between 5 and 7 genes appear to be needed, although some others, clustered with them, might play a role as well (Maqueda et al 2008;Gabrielsen et al 2014). Most proteins are hydrophobic, thus suggesting that bacteriocin synthesis is membrane associated.…”
Section: Genetics and Regulation Of Bacteriocin Synthesismentioning
confidence: 95%
“…This conformation makes them very resistant to heat (some retain their activity after treatment at 121°C for 15 min), pH variation, and proteolytic digestion. Two subgroups have been recognized based on their physicochemical characteristics; the first comprises cationic peptides with isoelectric points close to 10, its model bacteriocin being AS-48, while the second has isoelectric points close to neutrality or clearly in the acid range (gassericin A and butyrivibriocin A respectively) (Sánchez-Hidalgo et al 2011;Gabrielsen et al 2014).…”
mentioning
confidence: 99%
“…Circular bacteriocins are bactericidal toward their target bacterial cells. Similar to many other bacteriocins, circular bacteriocins apply their killing mechanism toward their target bacteria by permeation of the bacterial cell membrane, resulting in the leakage of ions, dissipation of membrane potential, and eventually in cell death (Gabrielsen et al 2014). Studies on the mode of action on enterocin AS-48, gassericin A, subtilosin A, and carnocyclin A have suggested that circular bacteriocins do not require a receptor molecule for their activity.…”
Section: Class Iic Bacteriocins (Circular Bacteriocins)mentioning
confidence: 99%
“…Indeed, gassericin A, garvicin ML, lactocyclin Q and leucocyclin Q produced by LAB inhibit a range of Gram-positive bacteria including food spoilage bacteria and food pathogens [18]. The remarkable stability and activity of these bacteriocins is attributed to their head to tail cyclisation which confers the bacteriocins with increased protease and heat resistance [19,20]. Garvicin ML is a recently discovered circular bacteriocin produced by L. garvieae DCC43 isolated from a Mallard duck which inhibits L. garvieae [21].…”
Section: The Particular Expansion In Numbers Of Circular Bacteriocinsmentioning
confidence: 99%